VD_FINDINFO Arrêt / 2010 / 900 vom 2. Juni 2010 - VD Tribunal cantonal (2010)
PRIVATION DE LIBERTÉ À DES FINS D'ASSISTANCE, RECOURANT, TUTELLE | 369 CC, 397a al. 1 CC, 380 CPC, 393 CPC, 398a CPC, 398d CPC